STUDENTS' PERSPECTIVES IN TRANSLATING ENGLISH DESCRIPTIVE TEXTS INTO INDONESIAN FOR ENGLISH LANGUAGE EDUCATION DEPARTMENT STUDENTS - Irene Adryani Nababan; Anita Sitanggang (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
This research entitle “Students Perspective in Translating English Descriptive Text Into Indonesian of English Education Department Students at UHNP” will discuss about the student perspective by the sixth semester students of English Education Department at University of HKBP Nommensen Pematangsiantar in translating English descriptive text into Indonesian and the factors that make the students difficult in traslating the text. This research will conduct in University of HKBP Nommensen Pematangsiantar. The researchers will use qualitative method. The researchers will analyze the answer of questionaires which fill by the students and interview the students to find out the factors that make the students difficult in traslating the text. The population of this research is the sixth semester students of English Education Department at University of HKBP Nommensen Pematangsiantar. The total number of population is 74 students. Sample is selected by using purposive sampling technique. Total sample is 33 students to fill the questionaire and 6 students to interview. Questionnaire and interview is the instruments of this research in gathering data.